Enhancing Online Food Platform Promotion: Human Capital's Impact on Performance - Al Finas Galih Reggy Saputra (Indonesian Journal of Cultural and Community Development, 2023)
This study investigates the influence of Human Capital on the performance of employees responsible for promotions within an innovative online food ordering platform. Utilizing a quantitative approach, a saturated sample of 88 promotion section employees was surveyed. The findings, analyzed through simple regression, reveal a significant positive correlation between Human Capital and employee performance in promotions. The study underscores the importance of focused training and development initiatives for these employees, providing valuable insights for platform management seeking to optimize promotional efforts and overall company performance. Highlight: The study examines the impact of Human Capital on the promotional performance of employees in an online food platform, highlighting the critical role of workforce capabilities. A comprehensive survey of 88 promotion section employees offers insights into the relationship between Human Capital and promotional effectiveness, emphasizing empirical evidence. The findings emphasize the strategic importance of targeted training and development programs for employees responsible for promotions, providing actionable recommendations for platform management to enhance overall performance. Keyword: Human Capital, Employee Performance, Online Food Platform, Promotion Section, Training and Development